Integrating science for water security governance - Kristen M. Whitney; Rebecca M. Peters; Anil Mishra; Annalise G. Blum; Perry C. Oddo; Kate A. Brauman; Angelica L. Gutierrez; John D. Bolten; Matthew J. McCarthy; Andrés Sánchez (Global Environmental Change, 2026)

Critical choices for nature assessment design in emerging environmental markets - S.J. Capon; J. Brazil-Boast; J.A. Fitzsimons; J. McDonald; S.M. Prober; R. Trebilco; I. Cresswell; J. Perry; M. Bachmann; J. Pittock; C. Hunter; T.J. Eyre (Environmental Development, 2026)

Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.

Variable pH habitats could help prepare stone crabs for coastal acidification - Philip M. Gravinese; Hannah E. Craft; Alex Douwes; Gretchen S. Faraci; Morgan L. Jarrett; Shelby A. Perry; Chloe E. Potts; Emma C. Rosser; Abigail L. Smith; Alexis R. Trevillian; Christopher Moore; Kimberly K. Yates (Marine Biology, 2026)

Assessing Recovery: Examination of Greenhouse Gas Fluxes, Soil Characteristics, and Vegetation in Sediment Enhanced Marshes - Danielle C. Perry; Nia Bartolucci; Cathleen Wigand; Kenneth B. Raposa; Joseph Loffredo; Wenley Ferguson; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Who needs closure? Estimating abundance with a Markovian availability model for geographically open removal sampling - Russell W. Perry; Adam C. Pope; A. Noble Hendrix; Joseph E. Kirsch; Bryan G. Matthias; Michael J. Dodrill (Ecology, 2026)
Removal sampling is an important method for estimating abundance, but nearly all removal models assume closure during sampling. Yet, closure may be difficult to assume, evaluate, or enforce in many settings. To address situations where populations are geographically open between each removal sample, we incorporated a Markovian availability process into an N‐mixture model framework. This model relates local abundance available for sampling to a superpopulation through recruitment of new individuals to the sampling area. To test the model, we (1) conducted parameter identifiability analysis, (2) fit the model to removal data generated from a random walk movement model, and (3) analyzed a case study of empirical removal data. Parameters were increasingly identifiable as capture probability exceeded 0.25 and removal samples increased from 3 to 6. Abundance estimates were unbiased when parameters were identifiable, except for scenarios that simulated a behavioral response to sampling. For our case study, the model estimated negligible recruitment for benthic‐oriented fishes, indicating closure, but we found evidence against closure for juvenile Chinook salmon, a highly mobile species. Our removal model allows researchers to formally test closure assumptions, to estimate the degree of closure, and to estimate abundance without bias when closure is violated.

Effect of transdermal melatonin on circulating cortisol and blood chemistry in horses exposed to transport stress - W.L. Crossland; E.O. Aviles-Rosa; E.B. Perry; C. Crowell; E. Webberson; J. Brown; J. Fassbender (Journal of Equine Veterinary Science, 2026)

A habitability lens to boost effective local climate adaptation - A.K. Magnan; V.K.E. Duvat; J. Bell; S.D. Donner; J.D. Ford; P.D. Nunn; C. Perry; T. Spencer; C.C.C. Wabnitz; I. White; J. Butler; A. McCarthy; et al. (Environmental Science & Policy, 2026)

Dynamic thumb localization and its adaptation: quantification with a novel robotic task - Luis Garcia-Fernandez; Andria J. Farrens; Christopher A. Johnson; Vicky Chan; Joel C. Perry; Eric T. Wolbrecht; David J. Reinkensmeyer (Experimental Brain Research, 2026)
The thumb plays a crucial role in hand function, yet its proprioceptive abilities remain poorly understood. Here we quantified dynamic thumb localization ability, as well as how this ability adapts to a perturbation, in unimpaired participants. For this, we developed a novel task in which a robot moved the thumb in a circle and participants pressed a button when they felt their thumb aligning with a target point on a screen, receiving visual error feedback in the form of a ball jumping toward the target after they pushed the button. The task also incorporated a propriovisual rotational perturbation to elicit and measure adaptation. To characterize thumb localization ability, we varied thumb speed and rotation diameter, assessed the effect of the propriovisual rotational perturbation, and compared index finger performance. Following task familiarization, average thumb localization error was relatively consistent, with a constant error (CE) of − 5.9°, variable error (VE) of 25.2°, and absolute error (AE) of 29.2°. Errors did not change significantly with speed or circle diameter. Reversing thumb rotation temporarily increased error followed by rapid error adaptation across the next 20 trials, as would be expected if individuals adapted using a body-centered (movement-aligned) frame of reference rather than a world-centered spatial frame. Localization error was comparable for the thumb and the index finger error for the same task and was correlated with a different, robotic assessment of finger proprioception (ρ = 0.61, p = 0.001). These findings indicate that dynamic thumb localization is somewhat inaccurate, although it can leverage visual feedback within a body-centered reference frame to adapt. Further, in unimpaired adults, the dynamic localization abilities of the thumb and index finger are related.

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Mitochondrial variation of long-tailed ducks, Clangula hyemalis, breeding and wintering in Iceland - Brynhildur Magnúsdóttir; Ölvir Styrmisson; Shaun C. Turnbull; Ib Krag Petersen; Matthew Perry; Diana V. Solovyeva; Petr Glazov; Arnþór Garðarsson; Jacob Höglund; Snæbjörn Pálsson (Aquatic Ecology, 2025)

Unravelling the novel mode of action of the spinosyn insecticides: A 25 year review - Trent Perry; Frank J. Wessels; Samantha Griffin; Chaoxian Geng; Natalie C. Giampietro; David G.J. Mann; Thomas C. Sparks (Pesticide Biochemistry and Physiology, 2025)

P12-32 Feasibility and Pilot Application of Cumulative Risk Assessment Approaches to Low- and No- Calorie Sweeteners - B.N. Rivera; C. Frankenfeld; C. Perry; D. Wikoff (Toxicology Letters, 2025)

Neighborhood environmental vulnerability factors strongly drove COVID-19 fatality and excess all-cause mortality in New York City, while long-term air pollutant associations were weak and varied - Alexander Azan; Sneha Kannoth; Cong Zhang; Mehr Shafiq; Earle C. Chambers; Perry E. Sheffield; Sandra S. Albrecht; Azure Thompson; Jennifer Woo Baidal; Min Qian; Stephanie Lovinsky-Desir; Jeanette A. Stingone (Science of The Total Environment, 2025)

Estimating coral reef carbonate budgets using Structure-from-Motion photogrammetry - Hannah C. Barkley; Ariel A. Halperin; Damaris Torres-Pulliza; Mia S. Lamirand; Courtney S. Couch; Candace E. Alagata; Rebecca M. Weible; Joy N. Smith; Thomas A. Oliver; Chris T. Perry (Coral Reefs, 2025)

Spinosyn resistance and cross-resistance – A 25 year review and analysis - Thomas C. Sparks; Frank J. Wessels; Trent Perry; Michael J. Price; Melissa W. Siebert; David G.J. Mann (Pesticide Biochemistry and Physiology, 2025)

Survival, Travel Time, and Use of Migration Routes by Juvenile Steelhead in a Modified River Estuary - Adam C. Pope; Russell W. Perry; Dalton J. Hance; Rebecca A. Buchanan (Estuaries and Coasts, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Structural plasticity of pyramidal cell neurons measured after FLASH and conventional dose-rate irradiation - Dara L. Dickstein; Richard Zhang; Ning Ru; Marie-Catherine Vozenin; Bayley C. Perry; Juan Wang; Janet E. Baulch; Munjal M. Acharya; Charles L. Limoli (Brain Structure and Function, 2025)
Evidence shows that ultra-high dose-rate FLASH-radiotherapy (FLASH-RT) provides relative protection against normal tissue complications and functional decrements in the irradiated brain. Past work has shown that radiation-induced cognitive impairment, neuroinflammation and reduced structural complexity ofgranule cell neurons were not observed to the same extent after FLASH-RT (> MGy/s) compared to conventional dose-rate (CONV, 0.1 Gy/s) delivery. In this study, we explored the sensitivity of hippocampal CA1 and medial prefrontal cortex (mPFC) pyramidal neurons to cranial irradiation and dose-rate modulation using electron and confocal microscopy. Neuron ultrastructural analyses by electron microscopy after 10 Gy FLASH- or CONV-RT exposures indicated that irradiation had little impact on dendritic complexity and synapse density in the CA1, but did increase the length and head diameter of smaller non-perforated synapses. Similarly, irradiation caused no change in mPFC prelimbic/infralimbic axospinous synapse density, but reductions in non-perforated synapse diameters. While irradiation resulted in thinner myelin sheaths compared to controls, none of these metrics were dose-rate sensitive. Analysis of fluorescently labeled CA1 neurons revealed no radiation-induced or dose-rate-dependent changes in overall dendritic complexity or spine density, in contrast to our past analysis of granule cell neurons. Super-resolution confocal microscopy following a clinical dosing paradigm (3 × 10 Gy) showed significant reductions in excitatory vesicular glutamate transporter 1 and inhibitory vesicular GABA transporter puncta density within the CA1 that were largely dose-rate independent. Collectively, these data reveal that, compared to granule cell neurons, CA1 and mPFC neurons are relatively more radioresistant irrespective of radiation dose-rate.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The mouse metabolic phenotyping center (MMPC) live consortium: an NIH resource for in vivo characterization of mouse models of diabetes and obesity - Maren Laughlin; Richard McIndoe; Sean H. Adams; Renee Araiza; Julio E. Ayala; Lucy Kennedy; Louise Lanoue; Louise Lantier; James Macy; Eann Malabanan; Owen P. McGuinness; Rachel Perry; et al. (Mammalian Genome, 2024)
The Mouse Metabolic Phenotyping Center (MMPC) Live Program was established in 2023 by the National Institute for Diabetes, Digestive and Kidney Diseases (NIDDK) at the National Institutes of Health (NIH) to advance biomedical research by providing the scientific community with standardized, high quality phenotyping services for mouse models of diabetes and obesity. Emerging as the next iteration of the MMPC Program which served the biomedical research community for 20 years (2001–2021), MMPC Live is designed as an outwardly-facing consortium of service cores that collaborate to provide reduced-cost consultation and metabolic, physiologic, and behavioral phenotyping tests on live mice for U.S. biomedical researchers. Four MMPC Live Centers located at universities around the country perform complex and often unique procedures in vivo on a fee for service basis, typically on mice shipped from the client or directly from a repository or vendor. Current areas of expertise include energy balance and body composition, insulin action and secretion, whole body carbohydrate and lipid metabolism, cardiovascular and renal function, food intake and behavior, microbiome and xenometabolism, and metabolic pathway kinetics. Additionally, an opportunity arose to reduce barriers to access and expand the diversity of the biomedical research workforce by establishing the VIBRANT Program. Directed at researchers historically underrepresented in the biomedical sciences, VIBRANT-eligible investigators have access to testing services, travel and career development awards, expert advice and experimental design consultation, and short internships to learn test technologies. Data derived from experiments run by the Centers belongs to the researchers submitting mice for testing which can be made publicly available and accessible from the MMPC Live database following publication. In addition to services, MMPC Live staff provide expertise and advice to researchers, develop and refine test protocols, engage in outreach activities, publish scientific and technical papers, and conduct educational workshops and training sessions to aid researchers in unraveling the heterogeneity of diabetes and obesity.

Coral carbonate production across depth: homogenisation after bleaching? - Sivajyodee Sannassy Pilly; Ronan C. Roche; Ines D. Lange; Chris T. Perry; Andrew O. M. Mogg; Kathryn Dawson; John R. Turner (Coral Reefs, 2024)
Recurrent climate-driven warming events, which can induce severe coral bleaching and mortality on tropical reefs, are predicted to cause homogenisation of coral communities and loss of ecosystem functions in shallow reef systems (< 30 m). However, data documenting the variation in coral carbonate production across depth are limited. Here we explore differences in coral cover, community composition, coral colony size structure and carbonate production rates between two depths (10 m and 17.5 m) across four atolls in the remote Chagos Archipelago. We show higher coral carbonate production rates at 10 m (4.82 ± 0.27 G, where G = kg CaCO 3 m −2 yr −1 ) compared to sites at 17.5 m (3.1 ± 0.18 G). The main carbonate producers at 10 m consisted of fast-growing branching and tabular corals (mainly Acroporids) and massive corals (mainly Porites ), with high abundances of medium- and large-sized colonies. In contrast, coral carbonate production at 17.5 m was driven by slow-growing encrusting and foliose morphotypes and small colony sizes. Utilising a dataset following 6–7 years of recovery after the 2015–2017 bleaching event, our results show that depth-homogenisation of coral communities was temporary and carbonate production rates at 10 m depth recovered quicker at 3 of 4 studied atolls. The exception is Great Chagos Bank where slower recovery of branching and tabular corals at 10 m has led to a longer-lasting depth-homogenisation of carbonate production rates. The latter example cautions that more frequent bleaching events may drive increasing homogenisation of carbonate production rates across depth gradients, with implications for vital reef geo-ecological functions.

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Three-dimensional imaging of martian glaciated terrain using Mars Reconnaissance Orbiter Shallow Radar (SHARAD) observations - Matthew R. Perry; Aaron T. Russell; Megan B. Russell; Frederick J. Foss; Frank C. Chuang; Gareth A. Morgan; Zachary M. Bain; Bruce A. Campbell; Nathaniel E. Putzig (Icarus, 2024)

Dynamic development of the Athabasca Valles outflow system from volcanic facies and 15 m scale roughness - Russell C. Miller; Cyril Grima; Sean P.S. Gulick; Timothy A. Goudge; Aaron T. Russell; Matthew R. Perry; Nathaniel E. Putzig; Bruce A. Campbell (Icarus, 2024)

Diet choice is insensitive to mating in male fruit flies - Mabel C. Sydney; Tracey Chapman; Jennifer C. Perry (Animal Behaviour, 2024)

Examining the stability of viral RNA and DNA in wastewater: Effects of storage time, temperature, and freeze-thaw cycles - Rachel C. Williams; William B. Perry; Kathryn Lambert-Slosarska; Ben Futcher; Cameron Pellett; India Richardson-O'Neill; Steve Paterson; Jasmine M.S. Grimsley; Matthew J. Wade; Andrew J. Weightman; Kata Farkas; Davey L. Jones (Water Research, 2024)

Within-field extrapolation away from a soil moisture probe using freely available satellite imagery and weather data - R. G. V. Bramley; E. M. Perry; J. Richetti; A. F. Colaço; D. J. Mowat; C. E. M. Ratcliff; R. A. Lawes (Precision Agriculture, 2024)
Recognition of the importance of soil moisture information to the optimisation of water-limited dryland cereal production has led to Australian growers being encouraged to make use of soil moisture sensors. However, irrespective of the merits of different sensing technologies, only a small soil volume is sensed, raising questions as to the utility of such sensors in broadacre cropping, especially given spatial variability in soil water holding capacity. Here, using data collected from contrasting sites in South Australia and Western Australia over two seasons, during which either wheat or barley were grown, we describe a method for extrapolating soil moisture information away from the location of a probe using freely-available NDVI time series and weather data as covariates. Relationships between soil moisture probe data, cumulative NDVI (ΣNDVI), cumulative net precipitation (ΣNP) and seasonal growing degree days (GDD) were significant ( P < 0.0001). In turn, these could be used to predict soil moisture status for any location within a field on any date following crop emergence. However, differences in ΣNDVI between different within-field zones did not fully explain differences in the soil moisture from multiple sensors located in these zones, resulting in different calibrations being required for each sensor or zone and a relatively low accuracy of prediction of measured soil moisture (R 2 adj ~ 0.4–0.7) which may not be sufficient to support targeted agronomic decision-making. The results also suggest that at any location within a field, the range of variation in soil moisture status down the soil profile on any given date will present as greater than the spatial variation in soil moisture across the field on that date. Accordingly, we conclude that, in dryland cereal cropping, the major value in soil moisture sensors arises from an enhanced ability to compare seasons and to relate similarities and differences between seasons as a guide to decision-making.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Impacts of olfactory cues on equine feeding behavior - Erin B. Perry; Grace C. Handlos; Jesse M. Fenton (Journal of Equine Veterinary Science, 2024)

Phylogenomic analyses of multidrug resistant Corynebacterium striatum strains isolated from patients in a tertiary care hospital in the UK - Vartul Sangal; Emma C. L. Marrs; Andrew Nelson; John D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Corynebacterium striatum is an emerging nosocomial pathogen. This is the first report showing the presence of three distinct multidrug resistant lineages of C. striatum among patients in a UK hospital. The presence of ErmX, Tet(W), Bla and AmpC proteins, and mutations in gyrA gene are associated with the resistance to clindamycin, doxycycline, penicillin and moxifloxacin, respectively. These strains are equipped with several corynebacterial virulence genes including two SpaDEF-type and a novel pilus gene cluster, which needs further molecular characterisation. This study highlights a need of developing an active surveillance strategy for routine monitoring and preventing potential cross-transmission among susceptible patients.

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

The chemotrophic behaviour of Aspergillus niger: Mapping hyphal filaments during chemo-sensing; the first step towards directed materials formation - Ayesha Sadaf; Matthias Brock; Carole C. Perry (Fungal Biology, 2024)

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Is our understanding of aquatic ecosystems sufficient to quantify ecologically driven climate feedbacks? - Corday R. Selden; Richard LaBrie; Laura C. Ganley; Daniel R. Crocker; Ohad Peleg; Danielle C. Perry; Hannah G. Reich; Matthew Sasaki; Patricia S. Thibodeau; Jana Isanta‐Navarro (Global Change Biology, 2024)
The Earth functions as an integrated system—its current habitability to complex life is an emergent property dependent on interactions among biological, chemical, and physical components. As global warming affects ecosystem structure and function, so too will the biosphere affect climate by altering atmospheric gas composition and planetary albedo. Constraining these ecosystem‐climate feedbacks is essential to accurately predict future change and develop mitigation strategies; however, the interplay among ecosystem processes complicates the assessment of their impact. Here, we explore the state‐of‐knowledge on how ecological and biological processes (e.g., competition, trophic interactions, metabolism, and adaptation) affect the directionality and magnitude of feedbacks between ecosystems and climate, using illustrative examples from the aquatic sphere. We argue that, despite ample evidence for the likely significance of many, our present understanding of the combinatorial effects of ecosystem dynamics precludes the robust quantification of most ecologically driven climate feedbacks. Constraining these effects must be prioritized within the ecological sciences for only by studying the biosphere as both subject and arbiter of global climate can we develop a sufficiently holistic view of the Earth system to accurately predict Earth's future and unravel its past.

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

A new approach to geostatistical synthesis of historical records reveals capuchin spatial responses to climate and demographic change - Odd T. Jacobson; Brendan J. Barrett; Susan E. Perry; Genevieve E. Finerty; Kate M. Tiedeman; Margaret C. Crofoot (Ecology Letters, 2024)
Recent proliferation of GPS technology has transformed animal movement research. Yet, time‐series data from this recent technology rarely span beyond a decade, constraining longitudinal research. Long‐term field sites hold valuable historic animal location records, including hand‐drawn maps and semantic descriptions. Here, we introduce a generalised workflow for converting such records into reliable location data to estimate home ranges, using 30 years of sleep‐site data from 11 white‐faced capuchin ( Cebus imitator ) groups in Costa Rica. Our findings illustrate that historic sleep locations can reliably recover home range size and geometry. We showcase the opportunity our approach presents to resolve open questions that can only be addressed with very long‐term data, examining how home ranges are affected by climate cycles and demographic change. We urge researchers to translate historical records into usable movement data before this knowledge is lost; it is essential to understanding how animals are responding to our changing world.

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

The Importance of Representative Sampling for Home Range Estimation in Field Primatology - Odd T. Jacobson; Margaret C. Crofoot; Susan Perry; Kosmas Hench; Brendan J. Barrett; Genevieve Finerty (International Journal of Primatology, 2024)
Understanding the amount of space required by animals to fulfill their biological needs is essential for comprehending their behavior, their ecological role within their community, and for effective conservation planning and resource management. The space-use patterns of habituated primates often are studied by using handheld GPS devices, which provide detailed movement information that can link patterns of ranging and space-use to the behavioral decisions that generate these patterns. However, these data may not accurately represent an animal’s total movements, posing challenges when the desired inference is at the home range scale. To address this problem, we used a 13-year dataset from 11 groups of white-faced capuchins ( Cebus capucinus imitator ) to examine the impact of sampling elements, such as sample size, regularity, and temporal coverage, on home range estimation accuracy. We found that accurate home range estimation is feasible with relatively small absolute sample sizes and irregular sampling, as long as the data are collected over extended time periods. Also, concentrated sampling can lead to bias and overconfidence due to uncaptured variations in space use and underlying movement behaviors. Sampling protocols relying on handheld GPS for home range estimation are improved by maximizing independent location data distributed across time periods much longer than the target species’ home range crossing timescale.

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

The University of West Florida Campus Ecosystem Study: effects of forest vegetation on light availability and soil processes - Frank S. Gilliam; Alayna L. Currey; Leo P. Young; Brenton C. Davis; Caden M. Perry (Environmental Monitoring and Assessment, 2024)

Evaluation of two beef cow fixed-time AI protocols that utilize presynchronization - Jaclyn N. Ketchum; Lacey K. Quail; Kaitlin M. Epperson; Chloey P. Guy; Jerica J.J. Rich; Saulo Menegatti Zoca; Adalaide C. Kline; Taylor N. Andrews; Julie A. Walker; Pedro Levy Piza Fontes; Sandy K. Johnson; Megan P.T. Owen; et al. (Theriogenology, 2024)

Distinctive hospital and community resistomes in Scottish urban wastewater: Metagenomics of a paired wastewater sampling design - Hannah C. Lepper; Meghan R. Perry; Bryan A. Wee; David Wills; Hanne Nielsen; Saria Otani; Moray Simon; Frank M. Aarestrup; Mark E.J. Woolhouse; Bram A.D. van Bunnik (Science of The Total Environment, 2023)

Nanoscale calcium uranyl carbonate clusters in water - Samuel N. Perry; Virginia G. Rodriguez; Peter C. Burns (Chemical Geology, 2023)

Geochemical fingerprinting to determine sediment source contribution and improve contamination assessment in mining-impacted floodplains in the Philippines - Justine Perry T. Domingo; Bryne T. Ngwenya; Mikaël Attal; Carlos Primo C. David; Simon M. Mudd (Applied Geochemistry, 2023)

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Using environmental health dialogue in a Diné-centered approach for individualized results reporting in an environmental exposure study following the Gold King Mine Spill - Yoshira Ornelas Van Horne; Stephanie Russo Carroll; Karletta Chief; Nathan Z. Lothrop; Jennifer R. Richards; Mae-Gilene Begay; Perry H. Charley; Jani C. Ingram; Paloma I. Beamer (Environmental Research, 2023)

Simulating the migration dynamics of juvenile salmonids through rivers and estuaries using a hydrodynamically driven enhanced particle tracking model - Vamsi Krishna Sridharan; Doug Jackson; Andrew M. Hein; Russell W. Perry; Adam C. Pope; Noble Hendrix; Eric M. Danner; Steven T. Lindley (Ecological Modelling, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Effect of post-harvest processing methods on the microbial safety of edible seaweed - Jessica G. Vorse; Colleen T. Moody; Lyle C. Massoia; Jennifer J. Perry; Kristin M. Burkholder; Carrie J. Byron (Journal of Applied Phycology, 2023)
The American seaweed industry is growing, primarily into the edible sector, and more seaweed products are available for human consumption. It is necessary to evaluate the safety of industry’s current post-harvest storage and processing methods to ensure the risk of foodborne pathogens on edible seaweed remains low. We evaluated the pathogen load of edible kelp post-harvest under three different storage temperatures (4˚C, 10˚C, 20˚C) and two different drying methods (air- and freeze-drying). The focal pathogens for this research included: Listeria monocytogenes, Salmonella enterica, Staphylococcus aureus, pathogenic Escherichia coli, Vibrio vulnificus and Vibrio parahaemolyticus . We tested all six pathogens under each treatment condition on both sugar kelp ( Saccharina latissima) and rockweed ( Ascophyllum nodosum ) as these are the most commonly farmed and wild-harvested species in Maine, respectively. We inoculated a known concentration of pathogen onto freshly harvested kelp, treated it under a storage temperature or drying method, and sampled it over time to determine the impact of treatment on pathogen load. Our results showed that storage at 20˚C can lead to replication while storage at 4˚C and 10˚C halted the replication of focal pathogens. Both air-drying and freeze-drying produced significant log scale reductions in surface pathogen load for all focal pathogens. Additionally, air-drying reduced pathogen load more than freeze-drying for a majority of pathogens and storing dried kelp for 6-weeks further reduced pathogen load across all cases. These results are promising for industry as they corroborate historical evidence that current post-harvest storage and processing conditions are producing products safe for human consumption.

Treatment of acid mine drainage and chromium (VI) removal using synthesised chitosan composites blended with kenaf fibre and γ-Fe2O3 nanoparticles - C. N. Nkuna; E. R. Sadiku; G. Perry; B. Oboirien; M. K. Dludlu; C. Thompson (International Journal of Environmental Science and Technology, 2023)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

The American Lobster Settlement Index: History, lessons, and future of a long-term, transboundary monitoring collaborative - M. Conor McManus; Damian C. Brady; Curtis Brown; Joshua T. Carloni; Melanie Giffin; Andrew G. Goode; Kristyn Kleman; Peter Lawton; Arnault Le Bris; Scott Olszewski; Derek N. Perry; Rémy Rochette; et al. (Frontiers in Marine Science, 2023)
Understanding the processes that influence recruitment variability in marine populations has been a long-standing challenge for resource management. Quantifying abundance at early life stages for marine fish and invertebrates with complex life histories can be difficult and require unconventional sampling approaches. However, the benefit of developing appropriate tools to sample early life stages is that, together with associated demographic and environmental information, the data can provide insights into the causes and consequences of recruitment variability, allowing prediction of older life stage abundance. Before the 1980s, the earliest benthic life stages of the American lobster ( Homarus americanus ) eluded quantitative field surveys. With the development of diver-based and vessel-deployed sampling methods over the past three decades, the American Lobster Settlement Index (ALSI) program has expanded into a regional, transboundary commitment to better understand lobster settlement processes and forecast future fishery trends for what has become the most valuable single-species fishery in North America. In this context, “settlement” is a shorthand for the annual recruitment of young-of-year lobster to coastal nurseries, as postlarvae settle to the seabed at the end of larval development. Here, we review the development and products of the ALSI program, first outlining the goals, methods, and data products of the program. We then highlight how the program has advanced the scientific knowledge on pre- and post-settlement processes that influence the fate of a cohort from egg hatch to harvest, which provides insight into the spawner-recruit relationship. Lastly, we provide guidance for future research recommendations building on the ALSI science to-date, some major elements of the program that have allowed for its success, and considerations for maintaining the ALSI program. By highlighting the uniqueness and contributions of the ALSI program, we hope it serves as a model for other scientists, managers, and industry collaborators aiming to understand recruitment processes for species over a broad geographic area.

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Challenges and solutions to biodiversity conservation in arid lands - Yuanming Zhang; Akash Tariq; Alice C. Hughes; Deyuan Hong; Fuwen Wei; Hang Sun; Jordi Sardans; Josep Peñuelas; Gad Perry; Jianfang Qiao; Alishir Kurban; Xiaoxia Jia; et al. (Science of The Total Environment, 2023)

Quantifying the effects of tides, river flow, and barriers on movements of Chinook Salmon smolts at junctions in the Sacramento – San Joaquin River Delta using multistate models - Michael J. Dodrill; Russell W. Perry; Adam C. Pope; Xiaochun Wang (Environmental Biology of Fishes, 2022)

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

Estimating rates of coral carbonate production from aerial and archive imagery by applying colony scale conversion metrics - E. Husband; C. T. Perry; I. D. Lange (Coral Reefs, 2022)
Recent interest in assessing coral reef functions has raised questions about how carbonate production rates have altered over the past few decades of ecological change. At the same time, there is growing interest in quantifying carbonate production on larger reef-scales. Resolving these issues is challenging because carbonate production estimates require three-dimensional survey data, which are typically collected in-situ over small spatial scales. In contrast, data that can be extracted from archive photograph or video imagery and high-resolution aerial imagery are generally planar. To address this disconnect, we collected data on the relationship between linear planar and 3D contour lengths of 62 common Indo-Pacific hard coral genera-morphotypes to establish appropriate conversion metrics (i.e. coral class rugosity values, hereafter termed R coral ). These conversion values allow planar colony dimensions to be converted to estimates of 3D colony contour length, which can be employed within existing census budget methodologies like ReefBudget to estimate coral carbonate production (G, in kg CaCO 3 m −2 yr −1 ). We tested this approach by comparing in-situ carbonate production data collected using the ReefBudget methodology against estimates derived from converted colony length data from video imagery. The data show a high level of consistency with an error of ~ 10%. We then demonstrate potential applications of the conversion metrics in two examples, the first using time-series (2006 to 2018) photo-quadrat imagery from Moorea, and the second using high-resolution drone imagery across different reef flat habitats from the Maldives. Whilst some degree of error must necessarily be accepted with such conversion techniques, the approach presented here offers exciting potential to calculate coral carbonate production: (1) from historical imagery to constrain past coral carbonate production rates; (2) from high quality aerial imagery for spatial up-scaling exercises; and (3) for use in rapid photograph or video-based assessments along reef systems where detailed surveys are not possible.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Factors affecting year‐class strength and growth of lake whitefish ( Coregonus clupeaformis ) in impounded lakes as revealed by otolith chronologies - Robert C. Perry; John M. Casselman (Journal of Fish Biology, 2022)
Recruitment and growth rates for lake whitefish ( Coregonus clupeaformis ) inhabiting the Smallwood Reservoir, Labrador, Canada, were influenced by facets of its creation and the temporal variability in water levels associated with its operation. Filling of the reservoir between 1971 and 1974 created a concurrent increase in lake whitefish recruitment above long‐term averages. In addition, recruitment was influenced by winter drawdown levels: higher water levels during February enhanced recruitment, accounting for an additional 10% of the long‐term variation in recruitment. Using otolith increments as a growth index, the authors determined that growth was influenced by reservoir creation. Growth rates during the initial period of flooding (1971–1975) exceeded long‐term averages and were greater than those in any other 5‐year period between 1965 and 1995. Growth rate increases were attributed to a simultaneous zooplankton bloom. After exceptional growth, lake whitefish showed a period (1976–1980) when growth rates decreased. The authors developed a quantitative technique using otoliths as an index to establish chronologies of fish growth rates. The index can be used to quantify and assess the impacts of reservoir hydrology on fish populations.

Caribbean king crab larvae and juveniles show tolerance to ocean acidification and ocean warming - Philip M. Gravinese; Shelby A. Perry; Angelo Jason Spadaro; Albert E. Boyd; Ian C. Enochs (Marine Biology, 2022)
Coastal habitats are experiencing decreases in seawater pH and increases in temperature due to anthropogenic climate change. The Caribbean king crab, Maguimithrax spinosissimus , plays a vital role on Western Atlantic reefs by grazing macroalgae that competes for space with coral recruits. Therefore, identifying its tolerance to anthropogenic stressors is critically needed if this species is to be considered as a potential restoration management strategy in coral reef environments. We examined the effects of temperature (control: 28 °C and elevated: 31 °C) and pH (control: 8.0 and reduced pH: 7.7) on the king crab’s larval and early juvenile survival, molt-stage duration, and morphology in a fully crossed laboratory experiment. Survival to the megalopal stage was reduced (13.5% lower) in the combined reduced pH and elevated temperature treatment relative to the control. First-stage (J1) juveniles delayed molting by 1.5 days in the reduced pH treatment, while second-stage (J2) crabs molted 3 days earlier when exposed to elevated temperature. Juvenile morphology did not differ among treatments. These results suggests that juvenile king crabs are tolerant to changes associated with climate change. Given the important role of the king crab as a grazer of macroalgae, its tolerance to climate stressors suggests that it could benefit restoration efforts aimed at making coral reefs more resilient to increasingly warm and acidic oceans into the future.

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Murine allele and transgene symbols: ensuring unique, concise, and informative nomenclature - M. N. Perry; C. L. Smith (Mammalian Genome, 2022)
In addition to naturally occurring sequence variation and spontaneous mutations, a wide array of technologies exist for modifying the mouse genome. Standardized nomenclature, including allele, transgene, and other mutation nomenclature, as well as persistent unique identifiers (PUID) are critical for effective scientific communication, comparison of results, and integration of data into knowledgebases such as Mouse Genome Informatics (MGI), Alliance for Genome Resources, and International Mouse Strain Resource (IMSR). As well as being the authoritative source for mouse gene, allele, and strain nomenclature, MGI integrates published and unpublished genomic, phenotypic, and expression data while linking to other online resources for a complete view of the mouse as a valuable model organism. The International Committee on Standardized Genetic Nomenclature for Mice has developed allele nomenclature rules and guidelines that take into account the number of genes impacted, the method of allele generation, and the nature of the sequence alteration. To capture details that cannot be included in allele symbols, MGI has further developed allele to gene relationships using sequence ontology (SO) definitions for mutations that provide links between alleles and the genes affected. MGI is also using (HGVS) variant nomenclature for variants associated with alleles that will enhance searching for mutations and will improve cross-species comparison. With the ability to assign unique and informative symbols as well as to link alleles with more than one gene, allele and transgene nomenclature rules and guidelines provide an unambiguous way to represent alterations in the mouse genome and facilitate data integration among multiple resources such the Alliance of Genome Resources and International Mouse Strain Resource.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

The Mechanical Response and Tolerance of the Anteriorly-Tilted Human Pelvis Under Vertical Loading - R. S. Salzar; E. M. Spratley; K. A. Henderson; P. C. Greenhalgh; J. Z. Zhang; B. J. Perry; J. A. McMahon (Annals of Biomedical Engineering, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Vacant lot soil degradation and mowing frequency shape communities of belowground invertebrates and urban spontaneous vegetation - Kayla I. Perry; Nicole C. Hoekstra; Steve W. Culman; Mary M. Gardiner (Urban Ecosystems, 2021)

A resource-poor developmental diet reduces adult aggression in male Drosophila melanogaster - Danielle Edmunds; Stuart Wigby; Jennifer C. Perry (Behavioral Ecology and Sociobiology, 2021)
Aggressive behaviours occur throughout the animal kingdom and agonistic contests often govern access to resources. Nutrition experienced during development has the potential to influence aggressive behaviours in adults through effects on growth, energy budgets and an individual’s internal state. In particular, resource-poor developmental nutrition might decrease adult aggression by limiting growth and energy budgets, or alternatively might increase adult aggression by enhancing motivation to compete for resources. However, the direction of this relationship—and effects of developmental nutrition experienced by rivals—remains unknown in most species, limiting understanding of how early-life environments contribute to variation in aggression. We investigated these alternative hypotheses by assessing male-male aggression in adult fruit flies, Drosophila melanogaster , that developed on a low-, medium- or high-resource diet, manipulated via yeast content. We found that a low-resource developmental diet reduced the probability of aggressive lunges in adults, as well as threat displays against rivals that developed on a low-resource diet. These effects appeared to be independent of diet-related differences in body mass. Males performed relatively more aggression on a central food patch when facing rivals of a low-resource diet, suggesting that developmental diet affects aggressive interactions through social effects in addition to individual effects. Our finding that resource-poor developmental diets reduce male-male aggression in D. melanogaster is consistent with the idea that resource budgets mediate aggression and in a mass-independent manner. Our study improves understanding of the links between nutrition and aggression. Significance statement Early-life nutrition can influence social behaviours in adults. Aggression is a widespread social behaviour with important consequences for fitness. Using the fruit fly, Drosophila melanogaster , we show that a poor developmental diet reduces aspects of adult aggressive behaviour in males. Furthermore, males perform more aggression near food patches when facing rivals of poor nutrition. This suggests that early-life nutrition affects aggressive interactions through social effects in addition to individual effects.

Does blood flow limit acute hypoxia performance in larval zebrafish (Danio rerio)? - M. C. Hughes; S. F. Perry (Journal of Comparative Physiology B, 2021)

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2021)
Cross‐shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross‐shore transport in the shallow (~ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini‐Autonomous Underwater Explorers (M‐AUEs). The M‐AUEs were programmed to maintain a specified depth, and were deployed near a mooring. Transport of the M‐AUEs was predominantly onshore, with average velocities up to 14 cm s −1 . To put the M‐AUE deployments into a broader context, we simulated > 500 individual high‐frequency internal waves observed at the mooring over a 14‐d deployment; in each internal wave, we released both depth‐keeping and passive virtual larvae every meter in the vertical. After the waves' passage, depth‐keeping virtual larvae were usually found closer to shore than passive larvae released at the same depth. Near the top of the water column (3–5‐m depth), ~ 20% of internal waves enhanced onshore transport of depth‐keeping virtual larvae by ≥ 50 m, whereas only 1% of waves gave similar enhancements to passive larvae. Our observations and simulations showed that depth‐keeping behavior in high‐frequency internal waves resulted in enhanced onshore transport at the top of the water column, and reduced offshore dispersal at the bottom, compared to being passive. Thus, even weak depth‐keeping may allow larvae to reach nearshore adult habitats more reliably than drifting passively.

Stony Coral Tissue Loss Disease in Florida Is Associated With Disruption of Host–Zooxanthellae Physiology - Jan H. Landsberg; Yasunari Kiryu; Esther C. Peters; Patrick W. Wilson; Noretta Perry; Yvonne Waters; Kerry E. Maxwell; Lindsay K. Huebner; Thierry M. Work (Frontiers in Marine Science, 2020)
Samples from eight species of corals ( Colpophyllia natans , Dendrogyra cylindrus , Diploria labyrinthiformis , Meandrina meandrites , Montastraea cavernosa , Orbicella faveolata, Pseudodiploria strigosa , and Siderastrea siderea ) that exhibited gross clinical signs of acute, subacute, or chronic tissue loss attributed to stony coral tissue loss disease (SCTLD) were collected from the Florida Reef Tract during 2016–2018 and examined histopathologically. The hallmark microscopic lesion seen in all eight species was focal to multifocal lytic necrosis (LN) originating in the gastrodermis of the basal body wall (BBW) and extending to the calicodermis, with more advanced lesions involving the surface body wall. This was accompanied by other degenerative changes in host cells such as mucocyte hypertrophy, degradation and fragmentation of gastrodermal architecture, and disintegration of the mesoglea. Zooxanthellae manifested various changes including necrosis (cytoplasmic hypereosinophilia, pyknosis); peripheral nuclear chromatin condensation; cytoplasmic vacuolation accompanied by deformation, swelling, or atrophy; swollen accumulation bodies; prominent pyrenoids; and degraded chloroplasts. Polyhedral intracytoplasmic eosinophilic periodic acid–Schiff-positive crystalline inclusion bodies (∼1–10 μm in length) were seen only in M. cavernosa and P. strigosa BBW gastrodermis in or adjacent to active lesions and some unaffected areas (without surface lesions) of diseased colonies. Coccoidlike or coccobacilloidlike structures (Gram-neutral) reminiscent of microorganisms were occasionally associated with LN lesions or seen in apparently healthy tissue of diseased colonies along with various parasites and other bacteria all considered likely secondary colonizers. Of the 82 samples showing gross lesions of SCTLD, 71 (87%) were confirmed histologically to have LN. Collectively, pathology indicates that SCTLD is the result of a disruption of host–symbiont physiology with lesions originating in the BBW leading to detachment and sloughing of tissues from the skeleton. Future investigations could focus on identifying the cause and pathogenesis of this process.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Correction to: “Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta” - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2020)

A novel cross‐shore transport mechanism revealed by subsurface, robotic larval mimics: Internal wave deformation of the background velocity field - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Matthew H. Alford; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2020)
Coastal physical processes are essential for the cross‐shore transport of meroplanktonic larvae to their benthic adult habitats. To investigate these processes, we released a swarm of novel, trackable, subsurface vehicles, the Mini‐Autonomous Underwater Explorers (M‐AUEs), which we programmed to mimic larval depth‐keeping behavior. The M‐AUE swarm measured a sudden net onshore transport of 30–70 m over 15–20 min, which we investigated in detail. Here, we describe a novel transport mechanism of depth‐keeping plankton revealed by these observations. In situ measurements and models showed that, as a weakly nonlinear internal wave propagated through the swarm, it deformed surface‐intensified, along‐isopycnal background velocities downward, accelerating depth‐keeping organisms onshore. These higher velocities increased both the depth‐keepers' residence time in the wave and total cross‐shore displacement, leading to wave‐induced transports twice those of fully Lagrangian organisms and four times those associated with the unperturbed background currents. Our analyses also show that integrating velocity time series from virtual larvae or mimics moving with the flow yields both larger and more accurate transport estimates than integrating velocity time series obtained at a point (Eulerian). The increased cross‐shore transport of organisms capable of vertical swimming in this wave/background‐current system is mathematically analogous to the increase in onshore transport associated with horizontal swimming in highly nonlinear internal waves. However, the mechanism described here requires much weaker swimming speeds (mm s −1 vs. cm s −1 ) to achieve significant onshore transports, and meroplanktonic larvae only need to orient themselves vertically, not horizontally.

Determining the underlying structure of insular isolation measures - Zachary T. Carter; George L. W. Perry; James C. Russell (Journal of Biogeography, 2020)
Aim Island isolation is measured in many ways. We seek to determine what the underlying latent factors characterizing these measures are, in order to understand how they mechanistically drive island biogeographical patterns and in order to recommend the most parsimonious measures. We then test the discriminatory power of the identified components against hypotheses generated from the biogeographical patterns of invasive rats. Location The 890 offshore islands (≥1 hectare area) of the New Zealand archipelago (latitude: 34.1–47.3°S, longitude: 166.2–178.4°E). Taxon Mammals. Methods We identified 16 measures that have been frequently used to characterize isolation in the past, including Euclidean‐based distance metrics, landscape connectivity metrics derived from least‐cost and circuit theory modelling, landscape buffers, stepping stones and insular area. We used principal components analysis (PCA) to synthesize the underlying structure of insular isolation with respect to terrestrial mammal dispersal. Finally, we tested the discriminatory power of retained principal components (PCs) using permutational multivariate analyses of variance (PERMANOVA). Tests include comparison of historical rat distributions, islands targeted for rat eradication and islands reinvaded by rats. Results The underlying structure of island isolation as characterized in the 16 metrics was described by three independent PCA components. Variable clustering suggests that PC1 captured distance from the mainland source to the focal island (PC1 Distance), PC2 described stepping stones available along the dispersal pathway (PC2 Stepping Stones) and PC3 described the focal island's position in the landscape (PC3 Insular Network). Each discriminatory test affirmed its respective biogeographical pattern hypothesis. Main conclusions The three underlying components we identify form the basis of a robust description of insular isolation that is of broad importance to understanding island biogeography dynamics. Moreover, these components can be applied across taxa without extensive structural or functional assumptions because the highest loading variables are not biologically informed.

Floral abundance and richness drive beneficial arthropod conservation and biological control on golf courses - Adam G. Dale; Rebecca L. Perry; Grace C. Cope; Nicole Benda (Urban Ecosystems, 2020)

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Extreme spatial heterogeneity in carbonate accretion potential on a Caribbean fringing reef linked to local human disturbance gradients - Didier M. de Bakker; Fleur C. van Duyl; Chris T. Perry; Erik H. Meesters (Global Change Biology, 2019)
The capacity of coral reefs to maintain their structurally complex frameworks and to retain the potential for vertical accretion is vitally important to the persistence of their ecological functioning and the ecosystem services they sustain. However, datasets to support detailed along‐coast assessments of framework production rates and accretion potential do not presently exist. Here, we estimate, based on gross bioaccretion and bioerosion measures, the carbonate budgets and resultant estimated accretion rates (EAR) of the shallow reef zone of leeward Bonaire – between 5 and 12 m depth – at unique fine spatial resolution along this coast (115 sites). Whilst the fringing reef of Bonaire is often reported to be in a better ecological condition than most sites throughout the wider Caribbean region, our data show that the carbonate budgets of the reefs and derived EAR varied considerably across this ~58 km long fringing reef complex. Some areas, in particular the marine reserves, were indeed still dominated by structurally complex coral communities with high net carbonate production (>10 kg CaCO 3 m −2 year −1 ), high live coral cover and complex structural topography. The majority of the studied sites, however, were defined by relatively low budget states ( 3 m −2 year −1 ) or were in a state of net erosion. These data highlight the marked spatial heterogeneity that can occur in budget states, and thus in reef accretion potential, even between quite closely spaced areas of individual reef complexes. This heterogeneity is linked strongly to the degree of localized land‐based impacts along the coast, and resultant differences in the abundance of reef framework building coral species. The major impact of this variability is that those sections of reef defined by low‐accretion rates will have limited capacity to maintain their structural integrity and to keep pace with current projections of climate change induced sea‐level rise (SLR), thus posing a threat to reef functioning and biodiversity, potentially leading to trophic cascades. Since many Caribbean reefs are more severely degraded than those found around Bonaire, it is to be expected that the findings presented here are rather the rule than the exception, but the study also highlights the need for similar high spatial resolution (along‐coast) assessments of budget states and accretion rates to meaningfully explore increasing coastal risk at the country level. The findings also more generally underline the significance of reducing local anthropogenic disturbance and restoring framework building coral assemblages. Appropriately focussed local preservation efforts may aid in averting future large‐scale above reef water depth increases on Caribbean coral reefs and will limit the social and economic implications associated with the loss of reef goods and services.

Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.

Proximity of restored hedgerows interacts with local floral diversity and species' traits to shape long‐term pollinator metacommunity dynamics - Lauren C. Ponisio; Perry de Valpine; Leithen K. M’Gonigle; Claire Kremen (Ecology Letters, 2019)
Disconnected habitat fragments are poor at supporting population and community persistence; restoration ecologists, therefore, advocate for the establishment of habitat networks across landscapes. Few empirical studies, however, have considered how networks of restored habitat patches affect metacommunity dynamics. Here, using a 10‐year study on restored hedgerows and unrestored field margins within an intensive agricultural landscape, we integrate occupancy modelling with network theory to examine the interaction between local and landscape characteristics, habitat selection and dispersal in shaping pollinator metacommunity dynamics. We show that surrounding hedgerows and remnant habitat patches interact with the local floral diversity, bee diet breadth and bee body size to influence site occupancy, via colonisation and persistence dynamics. Florally diverse sites and generalist, small‐bodied species are most important for maintaining metacommunity connectivity. By providing the first in‐depth assessment of how a network of restored habitat influences long‐term population dynamics, we confirm the conservation benefit of hedgerows for pollinator populations and demonstrate the importance of restoring and maintaining habitat networks within an inhospitable matrix.

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

Traditional materials from new sources – conflicts in analytical methods for calcium carbonate - David J. Belton; Graham J. Hickman; Carole C. Perry (Food Additives & Contaminants: Part A, 2019)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Carbon dioxide enrichment alters predator avoidance and sex determination but only sex is mediated by GABAA receptors - Jean-Claude Abboud; Edgar A. Bartolome; Mayra Blanco; Annalise C. Kress; Ian Y. Ellis; Perry K. Yazzolino; Kamrin I. Sorensen; James R. Winslow; David A. Cleary; Hugh Lefcort (Hydrobiologia, 2019)

The role of reforestation in carbon sequestration - L. E. Nave; B. F. Walters; K. L. Hofmeister; C. H. Perry; U. Mishra; G. M. Domke; C. W. Swanston (New Forests, 2019)

Molecular signatures of divergence and selection in closely related pine taxa - Witold Wachowiak; Julia Zaborowska; Bartosz Łabiszak; Annika Perry; Giovanni M. Zucca; Santiago C. González-Martínez; Stephen Cavers (Tree Genetics & Genomes, 2018)

Novel ecological and climatic conditions drive rapid adaptation in invasive Florida Burmese pythons - Daren C. Card; Blair W. Perry; Richard H. Adams; Drew R. Schield; Acacia S. Young; Audra L. Andrew; Tereza Jezkova; Giulia I.M. Pasquesi; Nicole R. Hales; Matthew R. Walsh; Michael R. Rochford; Frank J. Mazzotti; et al. (Molecular Ecology, 2018)
Invasive species provide powerful in situ experimental systems for studying evolution in response to selective pressures in novel habitats. While research has shown that phenotypic evolution can occur rapidly in nature, few examples exist of genomewide adaptation on short “ecological” timescales. Burmese pythons ( Python molurus bivittatus ) have become a successful and impactful invasive species in Florida over the last 30 years despite major freeze events that caused high python mortality. We sampled Florida Burmese pythons before and after a major freeze event in 2010 and found evidence for directional selection in genomic regions enriched for genes associated with thermosensation, behaviour and physiology. Several of these genes are linked to regenerative organ growth, an adaptive response that modulates organ size and function with feeding and fasting in pythons. Independent histological and functional genomic data sets provide additional layers of support for a contemporary shift in invasive Burmese python physiology. In the Florida population, a shift towards maintaining an active digestive system may be driven by the fitness benefits of maintaining higher metabolic rates and body temperature during freeze events. Our results suggest that a synergistic interaction between ecological and climatic selection pressures has driven adaptation in Florida Burmese pythons, demonstrating the often‐overlooked potential of rapid adaptation to influence the success of invasive species.

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Measurement of Aquaculture Chemotherapeutants in Flocculent Matter Collected at a Hard-Bottom Dominated Finfish Site on the South Coast of Newfoundland (Canada) After 2 Years of Fallow - Dounia Hamoutene; Flora Salvo; Stefana N. Egli; Ali Modir-Rousta; Robyn Knight; Geoff Perry; Christina S. Bottaro; Suzanne C. Dufour (Frontiers in Marine Science, 2018)

Multiple abiotic factors correlate with parallel evolution in Australian soil burrowing cockroaches - Perry G. Beasley‐Hall; Timothy R. C. Lee; Harley A. Rose; Nathan Lo (Journal of Biogeography, 2018)
Aim The ways in which abiotic factors contribute to parallel evolution—the evolution of similar, derived phenotypes in independent, closely related lineages—remain understudied. Australian cockroaches of the subfamilies Panesthiinae (“wood feeders”) and Geoscapheinae (“soil burrowers”) are two closely related groups that provide a striking example of parallel evolution of burrowing behaviour. The ancestral wood‐feeding panesthiines migrated from Asia ~20 million years ago before soil burrowing was independently acquired multiple times in the derived geoscapheines. Here, we investigate whether specific abiotic factors were associated with the parallel evolution of soil burrowing behaviour, and whether divergence events of geoscapheines from panesthiine ancestors are consistent with niche conservatism or divergence. Location The Australian mainland, including the areas in which selected Australian Panesthiinae and Geoscapheinae cockroach species are distributed. Methods We generated environmental niche models for members of the Australian Geoscapheinae and Panesthiinae using presence‐only data and abiotic variables related to temperature, precipitation, and soil composition from BioClim and the Australian Soil Resource Information System. We used an existing phylogenetic framework to compare environmental niche models and tested for niche conservatism versus divergence. Morphological convergence was assessed by a regression analysis and principal components analysis of leg segment and body dimensions in soil burrowers and wood feeders. Results We found no relationship between niche similarity and time since divergence, and only limited evidence for phylogenetic signal with respect to the environmental variables examined. We found that soil burrowing behaviour is consistently correlated with thirteen abiotic factors associated with aridity, including a wider range of temperatures and lower precipitation levels. Evidence for convergence in leg morphology and body dimensions across soil burrowers was found. Main conclusions Our results are consistent with soil burrowing behaviour evolving in response to ancient aridification events following the arrival of the Panesthiinae in Australia. Our results suggest a scenario of niche divergence between soil burrowers and each of their wood feeding sister taxa. There is evidence for morphological convergence on a “shovel‐like” protibiotarsus in the Geoscapheinae that would aid in burrowing into soil.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Investigating the candidacy of the serotype specific rhamnan polysaccharide based glycoconjugates to prevent disease caused by the dental pathogen Streptococcus mutans - Frank St. Michael; Qingling Yang; Chantelle Cairns; Evgeny Vinogradov; Perry Fleming; Alexander C. Hayes; Annie Aubry; Andrew D. Cox (Glycoconjugate Journal, 2018)

Post-bleaching coral community change on southern Maldivian reefs: is there potential for rapid recovery? - C. T. Perry; K. M. Morgan (Coral Reefs, 2017)

First global molecular phylogeny and biogeographical analysis of two arachnid orders (Schizomida and Uropygi) supports a tropical Pangean origin and mid‐Cretaceous diversification - Ronald M. Clouse; Michael G. Branstetter; Perry Buenavente; Louise M. Crowley; Jesse Czekanski‐Moir; David Emmanuel M. General; Gonzalo Giribet; Mark S. Harvey; Daniel A. Janies; Alma B. Mohagan; Dave P. Mohagan; Prashant P. Sharma; et al. (Journal of Biogeography, 2017)
Aim We sought to illuminate the history of the arachnid orders Schizomida and Uropygi, neither of which have previously been subjected to global molecular phylogenetic and biogeographical analyses. Location Specimens used in this study were collected in all major tropical and subtropical areas where they are presently found, including the Americas, Africa, Australia and the Indo‐Pacific region. Methods From field‐collected specimens, we sequenced two nuclear and two mitochondrial markers, combined these with publicly available data, and conducted multi‐gene phylogenetic analyses on 240 Schizomida, 24 Uropygi and 12 other arachnid outgroups. Schizomid specimens included one specimen from the small family Protoschizomidae; other schizomid specimens were in Hubbardiidae, subfamily Hubbardiinae, which holds 289 of the order's 305 named species. We inferred ancestral areas using the Dispersal‐Extinction‐Cladogenesis model of range evolution, and we used fossil calibrations to estimate divergence times. Results We recovered monophyletic Schizomida and Uropygi as each other's sister group, forming the clade Thelyphonida, and terminals from the New World were usually positioned as the earliest diverging lineages. The ancestral area for schizomids reconstructed unambiguously to the region comprised of Mexico, Southern California and Florida (the xeric New World subtropics). Optimal trees suggested a single colonization of the Indo‐Pacific in both orders, although this did not receive bootstrap support. Molecular dating gave an Upper Carboniferous origin for each order, and a mid‐Cretaceous expansion of Schizomida, including the origin and initial diversification of those in the Indo‐Pacific. Main conclusions Ancestral area reconstructions, molecular dating and fossil evidence all support an Upper Carboniferous, tropical Pangean origin for Thelyphonida, Schizomida and perhaps Uropygi. Much of this region became unsuitable habitat for these arachnids during the breakup of Pangea, but they persisted in the area that is now Meso‐ and South America. From there they then expanded to the Indo‐Pacific, where schizomids today display an idiosyncratic combination of microendemism and long‐range dispersal.

Palaeoecological records of coral community development on a turbid, nearshore reef complex: baselines for assessing ecological change - J. A. Johnson; C. T. Perry; S. G. Smithers; K. M. Morgan; N. Santodomingo; K. G. Johnson (Coral Reefs, 2017)

The role of ecology, neutral processes and antagonistic coevolution in an apparent sexual arms race - Jennifer C. Perry; Colin J. Garroway; Locke Rowe (Ecology Letters, 2017)
Some of the strongest examples of a sexual ‘arms race’ come from observations of correlated evolution in sexually antagonistic traits among populations. However, it remains unclear whether these cases truly represent sexually antagonistic coevolution; alternatively, ecological or neutral processes might also drive correlated evolution. To investigate these alternatives, we evaluated the contributions of intersex genetic correlations, ecological context, neutral genetic divergence and sexual coevolution in the correlated evolution of antagonistic traits among populations of Gerris incognitus water striders. We could not detect intersex genetic correlations for these sexually antagonistic traits. Ecological variation was related to population variation in the key female antagonistic trait (spine length, a defence against males), as well as body size. Nevertheless, population covariation between sexually antagonistic traits remained substantial and significant even after accounting for all of these processes. Our results therefore provide strong evidence for a contemporary sexual arms race.

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2017)

Commentary: On the water footprint as an indicator of water use in food production - E. Fereres; F. J. Villalobos; F. Orgaz; M. I. Minguez; G. van Halsema; C. J. Perry (Irrigation Science, 2017)

Investigating potential effects of zooplankton grazing on diatom-inferred drought reconstructions - Courtney R. Wigdahl-Perry; Jasmine E. Saros; Sherilyn C. Fritz; C. T. Hess (Hydrobiologia, 2017)

Do birds vocalize at higher pitch in noise, or is it a matter of measurement? - Alejandro A. Ríos-Chelén; Ambria N. McDonald; Ayala Berger; Anna C. Perry; Alan H. Krakauer; Gail L. Patricelli (Behavioral Ecology and Sociobiology, 2017)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

Linking innovative measurement technologies (ConMon and Dataflow© systems) for high-resolution temporal and spatial dissolved oxygen criteria assessment - C. A. O’Leary; E. Perry; A. Bayard; L. Wainger; W. R. Boynton (Environmental Monitoring and Assessment, 2016)

Erratum to: New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Heart rate analysis by sparse representation for acute pain detection - Shai Tejman-Yarden; Ofer Levi; Alex Beizerov; Yisrael Parmet; Tu Nguyen; Michael Saunders; Zvia Rudich; James C. Perry; Dewleen G. Baker; Tobias Moeller-Bertram (Medical & Biological Engineering & Computing, 2016)

Prediction of the Export and Fate of Global Ocean Net Primary Production: The EXPORTS Science Plan - David A. Siegel; Ken O. Buesseler; Michael J. Behrenfeld; Claudia R. Benitez-Nelson; Emmanuel Boss; Mark A. Brzezinski; Adrian Burd; Craig A. Carlson; Eric A. D'Asaro; Scott C. Doney; Mary J. Perry; Rachel H. R. Stanley; et al. (Frontiers in Marine Science, 2016)

Isolation of a wide range of minerals from a thermally treated plant: Equisetum arvense, a Mare’s tale - Anna Sola-Rabada; Julia Rinck; David J. Belton; Annie K. Powell; Carole C. Perry (JBIC Journal of Biological Inorganic Chemistry, 2016)

An emerging role for gasotransmitters in the control of breathing and ionic regulation in fish - Steve Perry; Y. Kumai; C. S. Porteus; V. Tzaneva; R. W. M. Kwong (Journal of Comparative Physiology B, 2016)

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

Computational Modeling of Pathophysiologic Responses to Exercise in Fontan Patients - Ethan Kung; James C. Perry; Christopher Davis; Francesco Migliavacca; Giancarlo Pennati; Alessandro Giardini; Tain-Yen Hsia; Alison Marsden (Annals of Biomedical Engineering, 2015)

A model of skin inflammation in humans leads to a rapid and reproducible increase in the interferon response signature: a potential translational model for drug development - Marion C. Dickson; Valerie J. Ludbrook; Hayley C. Perry; Paul A. Wilson; Sam J. Garthside; Michael H. Binks (Inflammation Research, 2015)

Evaluation of a new chromogenic medium, chromID OXA-48, for recovery of carbapenemase-producing Enterobacteriaceae from patients at a university hospital in Turkey - P. Zarakolu; K. M. Day; H. E. Sidjabat; W. Kamolvit; C. V. Lanyon; S. P. Cummings; D. L. Paterson; M. Akova; J. D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Community structure and palaeoecological implications of calcareous encrusters on artificial substrates across a Mexican Caribbean reef - L. J. Hepburn; P. Blanchon; G. Murphy; L. Cousins; C. T. Perry (Coral Reefs, 2015)

An international ecological study of adult height in relation to cancer incidence for 24 anatomical sites - Yannan Jiang; Roger J. Marshall; Sarah C. Walpole; David Prieto-Merino; Dong-Xu Liu; Jo K. Perry (Cancer Causes & Control, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Development of 26 novel microsatellite makers for the round whitefish (Prosopium cylindraceum) and successful polymorphic cross-specific amplification of seven previously developed salmonid markers - Gregory R. McCracken; Kristen L. Wilson; Hilary T. Brewis; Meghan C. McBride; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Development and characterization of 36 novel microsatellite markers for lake chub (Couesius plumbeus) using illumina paired-end sequencing - Gregory R. McCracken; Hilary T. Brewis; Meghan C. McBride; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Analyses of trends in air temperature in the United Kingdom using gridded data series from 1910 to 2011 - M. John Prior; Matthew C. Perry (International Journal of Climatology, 2014)
Gridded temperature datasets covering the UK at 5 km × 5 km resolution have been analysed for temporal and spatial patterns of change and variability. Decadal‐scale variability is visualized by smoothing the data series using a kernel smoother. Trends have been analysed by comparing averages for a baseline period with averages for a recent period, as well as using linear regression. Spatial patterns of change have been mapped by calculating trends for each grid point. Monthly gridded datasets of daily maximum, minimum and mean air temperatures are available from 1910 to date. These show statistically significant increases for all parts of the UK , with the rate of change increasing from the north and west to the south and east. Seasonally, the least significant changes have occurred in the winter, with significant increases for most districts for all of the other seasons. Derived indices based on daily temperature are available from 1961 onwards. There have been significant decreases in heating degree days and increases in growing degree days for all districts, while changes in cooling degree days are less significant as the values are low and inter‐annual variability dominates. There have been significant decreases in frost days, especially in spring and autumn, and this is linked to significant increases in growing season length, especially for Scotland.

Alcohol exposure inhibits adult neural stem cell proliferation - Joannalee C. Campbell; Tamara Stipcevic; Roberto E. Flores; Canelda Perry; Tod E. Kippin (Experimental Brain Research, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Genetics and mapping of quantitative traits for nodule number, weight, and size in soybean (Glycine max L.[Merr.]) - Sadal Hwang; Jeffery D. Ray; Perry B. Cregan; C. Andy King; Marilynn K. Davies; Larry C. Purcell (Euphytica, 2014)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Rapid vertical accretion on a ‘young’ shore-detached turbid zone reef: Offshore Paluma Shoals, central Great Barrier Reef, Australia - C. T. Perry; S. G. Smithers; P. Gulliver (Coral Reefs, 2013)

Time-dependent effects of haloperidol on glutamine and GABA homeostasis and astrocyte activity in the rat brain - Glenn T. Konopaske; Nicolas R. Bolo; Alo C. Basu; Perry F. Renshaw; Joseph T. Coyle (Psychopharmacology, 2013)

Improvements to Rapfish: a rapid evaluation technique for fisheries integrating ecological and human dimensions a - T. J. Pitcher; M. E. Lam; C. Ainsworth; A. Martindale; K. Nakamura; R. I. Perry; T. Ward (Journal of Fish Biology, 2013)
This paper reports recent developments in Rapfish, a normative, scalable and flexible rapid appraisal technique that integrates both ecological and human dimensions to evaluate the status of fisheries in reference to a norm or goal. Appraisal status targets may be sustainability, compliance with a standard (such as the UN code of conduct for responsible fisheries) or the degree of progress in meeting some other goal or target. The method combines semi‐quantitative ( e.g . ecological) and qualitative ( e.g . social) data via multiple evaluation fields, each of which is assessed through scores assigned to six to 12 attributes or indicators: the scoring method allows user flexibility to adopt a wide range of utility relationships. For assessing sustainability, six evaluation fields have been developed: ecological, technological, economic, social, ethical and institutional. Each field can be assessed directly with a set of scored attributes, or several of the fields can be dealt with in greater detail using nested subfields that themselves comprise multidimensional Rapfish assessments ( e.g . the hierarchical institutional field encompasses both governance and management, including a detailed analysis of legality). The user has the choice of including all or only some of the available sustainability fields. For the attributes themselves, there will rarely be quantitative data, but scoring allows these items to be estimated. Indeed, within a normative framework, one important advantage with Rapfish is transparency of the rigour, quality and replicability of the scores. The Rapfish technique employs a constrained multidimensional ordination that is scaled to situate data points within evaluation space. Within each evaluation field, results may be presented as a two‐dimensional plot or in a one‐dimensional rank order. Uncertainty is expressed through the probability distribution of Monte‐Carlo simulations that use the c.l . on each original observation. Overall results of the multidisciplinary analysis may be shown using kite diagrams that compare different locations, time periods (including future projections) and management scenarios, which make policy trade‐offs explicit. These enhancements are now available in the R programming language and on an open website, where users can run Rapfish analyses by downloading the software or uploading their data to a user interface.

Principles of Biofouling Protection in Marine Sponges: A Model for the Design of Novel Biomimetic and Bio-inspired Coatings in the Marine Environment? - Werner E. G. Müller; Xiaohong Wang; Peter Proksch; Carole C. Perry; Ronald Osinga; Johan Gardères; Heinz C. Schröder (Marine Biotechnology, 2013)

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

Spatial and temporal variations in turbidity on two inshore turbid reefs on the Great Barrier Reef, Australia - N. K. Browne; S. G. Smithers; C. T. Perry (Coral Reefs, 2013)

Estimating rates of biologically driven coral reef framework production and erosion: a new census-based carbonate budget methodology and applications to the reefs of Bonaire - C. T. Perry; E. N. Edinger; P. S. Kench; G. N. Murphy; S. G. Smithers; R. S. Steneck; P. J. Mumby (Coral Reefs, 2012)

To what extent do improved irrigation technologies extend aquifer life? - C. J. Perry; P. J. G. J. Hellegers (Hydrogeology Journal, 2012)

The effects of gill remodeling on transepithelial sodium fluxes and the distribution of presumptive sodium-transporting ionocytes in goldfish (Carassius auratus) - Julia C. Bradshaw; Yusuke Kumai; Steve F. Perry (Journal of Comparative Physiology B, 2012)

Vulnerability of riparian ecosystems to elevated CO 2 and climate change in arid and semiarid western N orth A merica - Laura G. Perry; Douglas C. Andersen; Lindsay V. Reynolds; S. Mark Nelson; Patrick B. Shafroth (Global Change Biology, 2012)
Riparian ecosystems, already greatly altered by water management, land development, and biological invasion, are being further altered by increasing atmospheric CO 2 concentrations ([ CO 2 ]) and climate change, particularly in arid and semiarid (dryland) regions. In this literature review, we (1) summarize expected changes in [ CO 2 ], climate, hydrology, and water management in dryland western N orth A merica, (2) consider likely effects of those changes on riparian ecosystems, and (3) identify critical knowledge gaps. Temperatures in the region are rising and droughts are becoming more frequent and intense. Warmer temperatures in turn are altering river hydrology: advancing the timing of spring snow melt floods, altering flood magnitudes, and reducing summer and base flows. Direct effects of increased [ CO 2 ] and climate change on riparian ecosystems may be similar to effects in uplands, including increased heat and water stress, altered phenology and species geographic distributions, and disrupted trophic and symbiotic interactions. Indirect effects due to climate‐driven changes in streamflow, however, may exacerbate the direct effects of warming and increase the relative importance of moisture and fluvial disturbance as drivers of riparian ecosystem response to global change. Together, climate change and climate‐driven changes in streamflow are likely to reduce abundance of dominant, native, early‐successional tree species, favor herbaceous species and both drought‐tolerant and late‐successional woody species (including many introduced species), reduce habitat quality for many riparian animals, and slow litter decomposition and nutrient cycling. Climate‐driven changes in human water demand and associated water management may intensify these effects. On some regulated rivers, however, reservoir releases could be managed to protect riparian ecosystem. Immediate research priorities include determining riparian species' environmental requirements and monitoring riparian ecosystems to allow rapid detection and response to undesirable ecological change.

Ω3-Polyunsaturated fatty acids prevent lipoperoxidation, modulate antioxidant enzymes, and reduce lipid content but do not alter glycogen metabolism in the livers of diabetic rats fed on a high fat thermolyzed diet - Adriano M. de Assis; Anderson Rech; Aline Longoni; Liane N. Rotta; Cristiane C. Denardin; Matheus A. Pasquali; Diogo O. Souza; Marcos L. S. Perry; José C. Moreira (Molecular and Cellular Biochemistry, 2012)

The lipid droplet coat protein perilipin 5 also localizes to muscle mitochondria - Madeleen Bosma; Ronnie Minnaard; Lauren M. Sparks; Gert Schaart; Mario Losen; Marc H. Baets; Hans Duimel; Sander Kersten; Perry E. Bickel; Patrick Schrauwen; Matthijs K. C. Hesselink (Histochemistry and Cell Biology, 2012)

Does low-intensity surface fire increase water- and nutrient-availability to overstorey Eucalyptus gomphocephala? - Dugald C. Close; Neil J. Davidson; Perry W. Swanborough; Ross Corkrey (Plant and Soil, 2011)

From Surviving to Thriving: A Health and Wellness Colloquium for Breast Cancer Survivors - Mark Stoutenberg; Stacy Cutrono; Arlette C. Perry (Journal of Cancer Education, 2011)

Sildenafil does not improve steady state cardiovascular hemodynamics, peak power, or 15-km time trial cycling performance at simulated moderate or high altitudes in men and women - Jochen Kressler; Mark Stoutenberg; Bernard A. Roos; Anne L. Friedlander; Arlette C. Perry; Joseph F. Signorile; Kevin A. Jacobs (European Journal of Applied Physiology, 2011)

Mercury in breeding saltmarsh sparrows (Ammodramus caudacutus caudacutus) - Oksana P. Lane; Kathleen M. O’Brien; David C. Evers; Thomas P. Hodgman; Andrew Major; Nancy Pau; Mark J. Ducey; Robert Taylor; Deborah Perry (Ecotoxicology, 2011)

Strategies for selection marker-free swine transgenesis using the Sleeping Beauty transposon system - Daniel F. Carlson; John R. Garbe; Wenfang Tan; Mike J. Martin; John R. Dobrinsky; Perry B. Hackett; Karl J. Clark; Scott C. Fahrenkrug (Transgenic Research, 2011)

Status and future of the forest health indicators program of the USA - Christopher William Woodall; Michael C. Amacher; William A. Bechtold; John W. Coulston; Sarah Jovan; Charles H. Perry; KaDonna C. Randolph; Beth K. Schulz; Gretchen C. Smith; Borys Tkacz; Susan Will-Wolf (Environmental Monitoring and Assessment, 2011)

Spatial variation in porosity and skeletal element characteristics in apical tips of the branching coral Acropora pulchra (Brook 1891) - R. C. Roche; R. L. Abel; K. G. Johnson; C. T. Perry (Coral Reefs, 2011)

Roles of cortisol and carbonic anhydrase in acid–base compensation in rainbow trout, Oncorhynchus mykiss - K. M. Gilmour; C. L. Collier; C. J. Dey; S. F. Perry (Journal of Comparative Physiology B, 2010)

Geomorphology and community structure of Middle Reef, central Great Barrier Reef, Australia: an inner-shelf turbid zone reef subject to episodic mortality events - N. K. Browne; S. G. Smithers; C. T. Perry (Coral Reefs, 2010)

Improving groundwater resource accounting in irrigated areas : a prerequisite for promoting sustainable use - S. S. D. Foster; C. J. Perry (Hydrogeology Journal, 2010)

Long-term coral community records from Lugger Shoal on the terrigenous inner-shelf of the central Great Barrier Reef, Australia - C. T. Perry; S. G. Smithers; K. G. Johnson (Coral Reefs, 2009)

Clinical and molecular epidemiology of ciprofloxacin-susceptible MRSA encoding PVL in England and Wales - M. J. Ellington; C. Perry; M. Ganner; M. Warner; I. McCormick Smith; R. L. Hill; L. Shallcross; S. Sabersheikh; A. Holmes; B. D. Cookson; A. M. Kearns (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Effects of 14 days of microgravity on fast hindlimb and diaphragm muscles of the rat - Mark D. Schuenke; David W. Reed; William J. Kraemer; Robert S. Staron; Jeff S. Volek; Wesley C. Hymer; Scott Gordon; L. Perry Koziris (European Journal of Applied Physiology, 2009)

A therapeutic dose of zolpidem reduces thalamic GABA in healthy volunteers: a proton MRS study at 4 T - Stephanie C. Licata; J. Eric Jensen; David M. Penetar; Andrew P. Prescot; Scott E. Lukas; Perry F. Renshaw (Psychopharmacology, 2009)

Combining remote sensing and economic analysis to support decisions that affect water productivity - P. J. G. J. Hellegers; R. Soppe; C. J. Perry; W. G. M. Bastiaanssen (Irrigation Science, 2009)

Filling the gap: improving estimates of working tree resources in agricultural landscapes - C. H. Perry; C. W. Woodall; G. C. Liknes; M. M. Schoeneberger (Agroforestry Systems, 2009)

Enhancing functional expression of heterologous lipase in the periplasm of Escherichia coli - Yali Xu; Amrita Yasin; Thomas Wucherpfennig; C. Perry Chou (World Journal of Microbiology and Biotechnology, 2008)

Carbonate budgets and reef production states: a geomorphic perspective on the ecological phase-shift concept - C. T. Perry; T. Spencer; P. S. Kench (Coral Reefs, 2008)

Effects of nicotine on sensorimotor gating impairment induced by long-term treatment with neurotoxic NMDA antagonism - Bruce A. Rasmussen; David C. Perry; Jahn O’Neil; Kebreten F. Manaye; Yousef Tizabi (Neurotoxicity Research, 2008)

The Neuroscience Information Framework: A Data and Knowledge Environment for Neuroscience - Daniel Gardner; Huda Akil; Giorgio A. Ascoli; Douglas M. Bowden; William Bug; Duncan E. Donohue; David H. Goldberg; Bernice Grafstein; Jeffrey S. Grethe; Amarnath Gupta; Maryam Halavi; David N. Kennedy; et al. (Neuroinformatics, 2008)

Effects of intermittent hypoxia on SaO2, cerebral and muscle oxygenation during maximal exercise in athletes with exercise-induced hypoxemia - Helen C. Marshall; Michael J. Hamlin; John Hellemans; Carissa Murrell; Nik Beattie; Ien Hellemans; Tracy Perry; Aimee Burns; Philip N. Ainslie (European Journal of Applied Physiology, 2008)

Seaglider observations of blooms and subsurface chlorophyll maxima off the Washington coast - M. J. Perry; B. S. Sackmann; C. C. Eriksen; C. M. Lee (Limnology and Oceanography, 2008)
From September 2003 to December 2007, autonomous, underwater Seaglider continuously ran a V‐shaped transect off Washington State from about 200‐m water depth (i.e., at the break between the shelf and slope) to offshore waters with depths >2700 m. Seaglider visited the offshore vertex at 47°N, 128°W, where our observations concentrated, approximately monthly. Seaglider measured temperature, conductivity, and dissolved oxygen to 1000 m and also recorded chlorophyll a (Chl a ) fluorescence and particulate optical backscatter to 150 m. Distinct interannual variation was documented in timing and depths of winter mixing, transition to a shallow summer pycnocline, and onset of mixed‐layer erosion in autumn. Chl a concentrations estimated from fluorescence were directly comparable among the seven laboratory‐calibrated sensors used, but their estimates exceeded concurrent, satellite‐derived concentrations by a factor of three. Seaglider optical profiles enabled interpretation of satellite imagery by revealing that the apparent autumn bloom after destratification was instead a vertical redistribution of phytoplankton from the subsurface maximum to a depth where they could be observed by satellites. Results of 4 yr of sampling within 25 km of the vertex demonstrate the value of gliders in ocean observing and their capability to carry out multiyear, fully autonomous operations under any sea state. The true power of glider programs will be realized in combination with other measurement platforms, including larger spatial coverage by satellites and more comprehensive biogeochemical measurements from moorings and occasional ship‐based sampling.

Introduction to the Limnology and Oceanography Special Issue on Autonomous and Lagrangian Platforms and Sensors (ALPS) - T. D. Dickey; E. C. Itsweire; M. A. Moline; M. J. Perry (Limnology and Oceanography, 2008)
This issue is devoted to recent developments of autonomous and Lagrangian platforms and sensors (ALPS) and their uses for solving a broad range of interdisciplinary aquatic problems. The collective papers treat a variety of problems that generally require measurements spanning a continuum of temporal and spatial scales. ALPS platforms in this issue include surface drifters, profiling and other types of subsurface floats, gliders, unmanned boats, autonomous underwater vehicles, and instrumented animals. ALPS platforms can provide access in difficult environments (e.g., under ice and in high‐sea states). They are also important for emerging networked ocean and lake observing systems that require continuous measurements and near‐real‐time data. This introductory paper provides historical perspectives, background, motivation for the issue, and a tabular summary of papers in the present collection.

High-throughput genotyping with the GoldenGate assay in the complex genome of soybean - David L. Hyten; Qijian Song; Ik-Young Choi; Mun-Sup Yoon; James E. Specht; Lakshmi K. Matukumalli; Randall L. Nelson; Randy C. Shoemaker; Nevin D. Young; Perry B. Cregan (Theoretical and Applied Genetics, 2008)

Exposure to traffic emissions throughout life and risk of breast cancer - N. M. Perry; P. C. Allgood; S. W. Duffy; K. Mokbel (Cancer Causes & Control, 2008)

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

Monoclonal antibodies reveal changes in predator efficiency with prey spatial pattern - GEORGIANNE J. K. GRIFFITHS; COLIN J. ALEXANDER; JOHN M. HOLLAND; PETER J. KENNEDY; JOE N. PERRY; WILLIAM O. C. SYMONDSON; LINTON WINDER (Molecular Ecology, 2008)
Spatially explicit predator–prey interactions can alter the predatory potential of natural enemies augmented through conservation biological control. To test hypotheses regarding such interactions and predatory efficiency, we used a combination of molecular techniques and mark–release–recapture to study the foraging behaviour of a generalist carabid predator, Poecilus cupreus , in response to spatial patterns of its cereal aphid prey ( Metapolophium dirhodum and Sitobion avenae ). Beetle and aphid numbers were measured across two grids of sampling locations, within which aphid spatial pattern had been manipulated to generate patchy and more homogenous distributions. Aphid consumption was measured by enzyme‐linked immunosorbent assays (ELISA) of beetle gut contents, using an aphid‐specific monoclonal antibody. Movement and distribution patterns suggest that P. cupreus does not aggregate at, nor instigate prey‐taxis within, aphid patches. However, more than two‐thirds of the 2169 P. cupreus tested by ELISA had consumed aphids and the proportion of beetles containing aphid proteins was positively related to aphid density. Against expectation, the proportion of predators feeding on aphids was greatest where prey were homogenously distributed, and this was attributed to the loss of partial refuges for prey in aphid patches. The functional value of this type of uniform foraging strategy is ideally suited to early colonization of the crop habitat, when aphid numbers are low, before populations build up and form strong spatial patterns.

The Environmental Polymorphisms Registry: a DNA resource to study genetic susceptibility loci - Patricia C. Chulada; Heather L. Vahdat; Richard R. Sharp; Tracy C. DeLozier; Paul B. Watkins; Susan N. Pusek; Perry J. Blackshear (Human Genetics, 2008)

Concentrations of the Allelochemical (±)-Catechin IN Centaurea maculosa Soils - Laura G. Perry; Giles C. Thelen; Wendy M. Ridenour; Ragan M. Callaway; Mark W. Paschke; Jorge M. Vivanco (Journal of Chemical Ecology, 2007)

Hopley D, Smithers SG, Parnell KE: The Geomorphology of the Great Barrier Reef: development, diversity, and change - C. T. Perry (Coral Reefs, 2007)

Steadiness of quadriceps contractions in young and older adults with and without a history of falling - Serena F. Carville; Mark C. Perry; Olga M. Rutherford; I Christopher H. Smith; Di J. Newham (European Journal of Applied Physiology, 2007)

Strength, power output and symmetry of leg muscles: effect of age and history of falling - Mark C. Perry; Serena F. Carville; I. Christopher H. Smith; Olga M. Rutherford; Di J. Newham (European Journal of Applied Physiology, 2007)

Calcium carbonate budgets for two coral reefs affected by different terrestrial runoff regimes, Rio Bueno, Jamaica - J. Mallela; C. T. Perry (Coral Reefs, 2007)

An assessment of the suitability of a plastic thermometer screen for climatic data collection - M. C. Perry; M. J. Prior; D. E. Parker (International Journal of Climatology, 2007)
For over a century, wooden thermometer screens of the Stevenson design have been used in the meteorological station network administered by the UK Met Office. A screen is now being manufactured of the same dimensions but made from plastic. This requires minimal maintenance and has the potential for a much longer life than the wooden type. In order to determine whether a changeover to the plastic type would be acceptable for climatological applications, in particular for studies of climate change, a 12‐month trial was carried out at 3 contrasting UK locations. Temperature and relative humidity measurements were made at 1‐minute intervals in plastic and wooden trial screens installed at each site, as well as in the existing operational wooden screens. At the start of the trial, acceptance criteria based on Global Climate Observing System (GCOS) standards were set for mean and extreme temperature values. The temperature differences between the trial wooden and plastic screens were all found to be within these acceptance criteria. The largest differences occurred between pairs of wooden screens, not between wooden and plastic screens. Analysis of humidity differences between wooden and plastic screens did not yield clear results. To help understand the temperature and humidity differences, the screen data were analysed in terms of other current weather conditions, principally solar radiation and wind speed. We recommend that, in temperate climates, the plastic thermometer screen is a climatologically consistent alternative to the wooden design, requiring no adjustments to long‐term records. © Crown Copyright 2006. Reproduced with the permission of the Controller of HMSO. Published by John Wiley & Sons, Ltd.

Long-term effects of developmental PCP administration on sensorimotor gating in male and female rats - Bruce A. Rasmussen; Jahn O’Neil; Kebreten F. Manaye; David C. Perry; Yousef Tizabi (Psychopharmacology, 2007)

Debate: “Is Increasing Neuroinflammation Beneficial for Neural Repair?” - Keith A. Crutcher; Howard E. Gendelman; Jonathan Kipnis; J. Regino Perez-Polo; V. H. Perry; Phillip G. Popovich; Lynne C. Weaver (Journal of Neuroimmune Pharmacology, 2006)

Functional properties of the titin/connectin-associated proteins, the muscle-specific RING finger proteins (MURFs), in striated muscle - Carol C. Gregorio; Cynthia N. Perry; Abigail S. McElhinny (Journal of Muscle Research and Cell Motility, 2006)

Prefrontal GABA levels in cocaine-dependent subjects increase with pramipexole and venlafaxine treatment - Chris C. Streeter; John Hennen; Yong Ke; J. Eric Jensen; Ofra Sarid-Segal; Leanne E. Nassar; Clifford Knapp; Angela A. Meyer; Tae Kwak; Perry F. Renshaw; Domenic A. Ciraulo (Psychopharmacology, 2006)

Overexpression of GRK2 in alzheimer disease and in a chronic hypoperfusion rat model is an early marker of brain mitochondrial lesions - Mark E. Obrenovich; Mark A. Smith; Sandra L. Siedlak; Shu G. Chen; Jack C. De La Torre; George Perry; Gjumrakch Aliev (Neurotoxicity Research, 2006)

Prefrontal GABA levels in cocaine-dependent subjects increase with pramipexole and venlafaxine treatment - Chris C. Streeter; John Hennen; Yong Ke; J. Eric Jensen; Ofra Sarid-Segal; Leanne E. Nassar; Clifford Knapp; Angela A. Meyer; Tae Kwak; Perry F. Renshaw; Domenic A. Ciraulo (Psychopharmacology, 2005)

Ladybird mothers mitigate offspring starvation risk by laying trophic eggs - Jennifer C. Perry; Bernard D. Roitberg (Behavioral Ecology and Sociobiology, 2005)

Disturbance frequency and community structure in a twenty-five year intervention study - Joel C. Trexler; William F. Loftus; Sue Perry (Oecologia, 2005)

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine - Hyun-Sang Cho; Deepak C. D’Souza; Ralitza Gueorguieva; Edward B. Perry; Steven Madonick; Laurence P. Karper; Anissa Abi-Dargham; Aysenil Belger; Walid Abi-Saab; Deborah Lipschitz; Alexandre Bennet; John P. Seibyl; et al. (Psychopharmacology, 2005)

Deconstruction of Historic Mercury Accumulation in Lake Sediments, Northeastern United States - Ethan Perry; Stephen A. Norton; Neil C. Kamman; P. M. Lorey; Charles T. Driscoll (Ecotoxicology, 2005)

Predicting Cotton Lint Yield Maps from Aerial Photographs - G. Vellidis; M. A. Tucker; C. D. Perry; D. L. Thomas; N. Wells; C. K. Kvien (Precision Agriculture, 2004)

Phosphonates and particulate organic phosphorus cycling in an anoxic marine basin - C. R. Benitez-Nelson; Lauren O'Neill; Lauren C. Kolowith; Perry Pellechia; Robert Thunell (Limnology and Oceanography, 2004)
Total particulate phosphorus (TPP), particulate inorganic P (PIP), and particulate organic P (POP) concentrations were measured in a year‐long series of sediment trap samples collected throughout the oxic‐anoxic water column (275 m, 455 m, 930 m, and 1,255 m) of the Cariaco Basin. TPP, PIP, and POP fluxes varied seasonally and decreased significantly with depth, from 65 to 19 µmol TPP m −2 d −1 , 43 to 8 µmol PIP m −2 d −1 , and 22 to 11 µmol POP m −2 d −1 . Significant flux relationships (p 31 P nuclear magnetic resonance (NMR), and it was found that phosphonates, chemically and thermally inert compounds, are a significant fraction of the TPP pool. Furthermore, these compounds were preferentially removed relative to more bioavailable P esters during a low flux event. Their selective removal suggests that these compounds may be an unrecognized source of bioavailable P under anoxic conditions.

QTL controlling partial resistance to Stagonospora nodorum leaf blotch in winter wheat cultivar Alba - Edward Arseniuk; Pawel C. Czembor; Andrzej Czaplicki; Qijian Song; Perry B. Cregan; David L. Hoffman; Peter P. Ueng (Euphytica, 2004)

Low doses of domoic acid during postnatal development produce permanent changes in rat behaviour and hippocampal morphology - T. A. Doucette; P. B. Bernard; H. Husum; M. A. Perry; C. L. Ryan; R. A. Tasker (Neurotoxicity Research, 2004)

Marginal and non-reef-building coral environments - C. T. Perry; P. Larcombe (Coral Reefs, 2003)

Biological degradation of coral framework in a turbid lagoon environment, Discovery Bay, north Jamaica - I. A. Macdonald; C. T. Perry (Coral Reefs, 2003)

The genetic architecture of correlations among growth‐related traits and male age at maturation in rainbow trout - C. J. Martyniuk; G. M. L. Perry; H. K. Mogahadam; M. M. Ferguson; R. G. Danzmann (Journal of Fish Biology, 2003)
Heritabilities and genetic correlations among growth‐related traits of two cultured strains (Rainbow Springs and Spring Valley) of rainbow trout Oncorhynchus mykiss were estimated using restricted maximum likelihood methods with a three‐generation pedigree. Heritability was high (>0·50 ± 0·03) for body mass and condition factor but moderate (0·35 ± 0·04) for age at sexual maturity in males. Body mass and age at sexual maturation were phenotypically correlated in the families of one experimental strain, Rainbow Springs, and had a positive genetic correlation (0·26 ± 0·03) across families from both test strains (Rainbow Springs and Spring Valley). This indicates that faster growing individuals were more likely to mature at 2 years of age than slower growing individuals in the two hatchery strains investigated. Microsatellite markers of body mass quantitative tract loci (QTL) were reconfirmed as being located on linkage groups B, G, N, 5 and new markers on Oi were detected. Some QTL effects were restricted to specific sampling dates suggesting temporal expression of QTL. QTL for condition factor were limited to linkage group G in both strains. Three suggestive QTL for precocious maturation mapped to similar regions as those for body mass in the Rainbow Springs families while no associations were evident in the Spring Valley families. The results suggest that these regions may play a role in the basis for genetic and phenotypic correlations between body mass and precocious maturation in this species.

Interspecific Interactions Between Cebus capucinus and Other Species: Data from Three Costa Rican Sites - Lisa M. Rose; Susan Perry; Melissa A. Panger; Katharine Jack; Joseph H. Manson; Julie Gros-Louis; Katherine C. Mackinnon; Erin Vogel (International Journal of Primatology, 2003)

A new mode of parental care in cockroaches - J. Perry; C. A. Nalepa (Insectes Sociaux, 2003)

?13C and water-use efficiency in Australian grasstrees and South African conifers over the last century - Perry W. Swanborough; Byron B. Lamont; Edmund C. February (Oecologia, 2003)

Role of vascular hypoperfusion-induced oxidative stress and mitochondria failure in the pathogenesis of Alzheimer disease - Gjumrakch Aliev; Mark A. Smith; Mark E. Obrenovich; Jack C. de la Torre; George Perry (Neurotoxicity Research, 2003)

Stable isotope systematics of two cenotes from the northern Yucatan Peninsula, Mexico - Richard A. Socki; Eugene Jr. C. Perry; Christopher S. Romanek (Limnology and Oceanography, 2002)
Deep water‐filled sinkholes, cenotes, are common in the northern Yucatan Peninsula. At least five of these cenotes are deep enough to extend through a freshwater lens of meteoric origin in which δ 18 O and δD follow the trend δD = 8.11 × δ 18 O + 10.4. Below this freshwater lies saline water that originated as seawater and has retained its seawater isotopic identity. Deep cenotes, characterized by input of variable amounts of organic debris from tropical vegetation and by poor circulation below the fresh‐/saltwater interface, provide excellent water columns in which to study sulfur redox phenomena. Measurements include O, H, and S isotope composition, conductivity, sulfur speciation, and pH from two cenotes (Ucil, 98 m deep, and Xcolac, 125 m deep). Strong 34S enrichment of sulfate and 34 S depletion of sulfide indicate anaerobic bacterial reduction of sulfate. A shift in the isotopic composition of sulfur in Xcolac from a seawater value of +21.0‰ (CDT) to +41.8‰ indicates conversion of sulfate to isotopically light sulfide. Mass balance calculations indicate that escape of isotopically light sulfur from the system is a slow process. At 80 m in Xcolac, a difference in sulfur isotope composition between sulfate and sulfide (△34S) of 63.2‰ is observed and could be the result of multiple sulfate reduction reactions. Higher in the water column, sulfide oxidation occurs, probably the result of bacterially mediated sulfide oxidation processes. A deep observation well (lacking organic matter input) shows only a slight deviation in sulfur isotope composition of sulfate from seawater values.

Planktonic copepods from temporary marshes in Everglades National Park (Florida, U.S.A.) - M. C. Bruno; G. Sagnotti; S. A. Perry (Hydrobiologia, 2002)

Call for submission of manuscripts - C. Perry; P. Larcombe (Coral Reefs, 2002)

The effects of endothelin-1 on the cardiorespiratory physiology of the freshwater trout ( Oncorhynchus mykiss ) and the marine dogfish ( Squalus acanthias ) - Perry S.; Montpetit C.; McKendry J.; Desforges P.R.; Gilmour K.; Wood C.; Olson K. (Journal of Comparative Physiology B, 2001)

Storm-induced coral rubble deposition: Pleistocene records of natural reef disturbance and community response. - C. Perry (Coral Reefs, 2001)

Intracellular vesicular trafficking in the gill epithelium of urea-excreting fish - P. Laurent; C. M. Wood; Y. Wang; S. F. Perry; K. M. Gilmour; P. Part; C. Chevalier; M. West; P. J. Walsh (Cell and Tissue Research, 2001)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)

Biosilicification: the role of the organic matrix in structure control - Carole C. Perry; Tracey Keeling-Tucker (JBIC Journal of Biological Inorganic Chemistry, 2000)

The influence of chronic anaemia on catecholamine secretion in the rainbow trout ( Oncorhynchus mykiss ) - S. F. Perry; C. J. Montpetit; A. E. Julio; K. Moore (Journal of Comparative Physiology B, 1999)

The major brain isoform of Kif1b lacks the putative mitochondria-binding domain - Laura Conforti; E. Anne Buckmaster; Andrea Tarlton; Michael C. Brown; Mary F. Lyon; V. Hugh Perry; Michael P. Coleman (Mammalian Genome, 1999)

Transferring soils from high‐ to low‐elevation forests increases nitrogen cycling rates: climate change implications - Stephen C. Hart; David A. Perry (Global Change Biology, 1999)
We assessed the potential impact of global warming resulting from a doubling of preindustrial atmospheric CO 2 on soil net N transformations by transferring intact soil cores (0–15 cm) from a high‐elevation old‐growth forest to a forest about 800 m lower in elevation in the central Oregon Cascade Mountains, USA. The lower elevation site had mean annual air and soil (10‐cm mineral soil depth) temperatures about 2.4 and 3.9 °C higher than the high‐elevation site, respectively. Annual rates of soil net N mineralization and nitrification more than doubled in soil transferred to the low‐elevation site (17.2–36.0 kg N ha –1 and 5.0–10.7 kg NO 3 – –N ha –1 , respectively). Leaching of inorganic N from the surface soil (in the absence of plant uptake) also increased. The reciprocal treatment (transferring soil cores from the low‐ to the high‐elevation site) resulted in decreases of about 70, 80, and 65% in annual rates of net N mineralization, nitrification, and inorganic N leaching, respectively. Laboratory incubations of soils under conditions of similar temperature and soil water potential suggest that the quality of soil organic matter is higher at the high‐elevation site. Similar in situ rates of soil net N transformations between the two sites occurred because the lower temperature counteracts the effects of greater substrate quantity and quality at the high elevation site. Our results support the hypothesis that high‐elevation, old‐growth forest soils in the central Cascades have higher C and N storage than their low‐elevation analogues primarily because low temperatures limit net C and N mineralization rates at higher elevations.

Macroborers within coral framework at Discovery Bay, north Jamaica: species distribution and abundance, and effects on coral preservation - C. T. Perry (Coral Reefs, 1998)

The effects of arginine vasotocin and catecholamines on nitrogen excretion and the cardio-respiratory physiology of the gulf toadfish, Opsanus beta - S. F. Perry; K. M. Gilmour; C. M. Wood; P. Pärt; P. Laurent; P. J. Walsh (Journal of Comparative Physiology B, 1998)

Polymorphic tetranucleotide repeat site within intron 7 of the β-amyloid precursor protein gene and its lack of association with Alzheimer's disease - Ling Li; Rodney Perry; Jianming Wu; D. Pham; Tauni Ohman; Lindy E. Harrell; Rodney C. P. Go; K. Fukuchi (Human Genetics, 1998)

Cocaine decreases relative cerebral blood volume in humans: a dynamic susceptibility contrast magnetic resonance imaging study - M. J. Kaufman; Jonathan M. Levin; Luis C. Maas; Stephanie L. Rose; Scott E. Lukas; Jack H. Mendelson; Bruce M. Cohen; Perry F. Renshaw (Psychopharmacology, 1998)

Population structure of nuclear and mitochondrial DNA variation among humpback whales in the North Pacific - C. S. BAKER; L. MEDRANO‐GONZALEZ; J. CALAMBOKIDIS; A. PERRY; F. PICHLER; H. ROSENBAUM; J. M. STRALEY; J. URBAN‐RAMIREZ; M. YAMAGUCHI; O. VON ZIEGESAR (Molecular Ecology, 1998)
The population structure of variation in a nuclear actin intron and the control region of mitochondrial DNA is described for humpback whales from eight regions in the North Pacific Ocean: central California, Baja Peninsula, nearshore Mexico (Bahia Banderas), offshore Mexico (Socorro Island), southeastern Alaska, central Alaska (Prince Williams Sound), Hawaii and Japan (Ogasawara Islands). Primary mtDNA haplotypes and intron alleles were identified using selected restriction fragment length polymorphisms of target sequences amplified by the polymerase chain reaction (PCR–RFLP). There was little evidence of heterogeneity in the frequencies of mtDNA haplotypes or actin intron alleles due to the year or sex composition of the sample. However, frequencies of four mtDNA haplotypes showed marked regional differences in their distributions (Φ ST = 0.277; P n = 205 individuals) while the two alleles showed significant, but less marked, regional differences (Φ ST = 0.033; P n = 400 chromosomes). An hierarchical analysis of variance in frequencies of haplotypes and alleles supported the grouping of six regions into a central and eastern stock with further partitioning of variance among regions within stocks for haplotypes but not for alleles. Based on available genetic and demographic evidence, the southeastern Alaska and central California feeding grounds were selected for additional analyses of nuclear differentiation using allelic variation at four microsatellite loci. All four loci showed significant differences in allele frequencies (overall F ST = 0.043; P n = 139 chromosomes per locus), indicating at least partial reproductive isolation between the two regions as well as the segregation of mtDNA lineages. Although the two feeding grounds were not panmictic for nuclear or mitochondrial loci, estimates of long‐term migration rates suggested that male‐mediated gene flow was several‐fold greater than female gene flow. These results include and extend the range and sample size of previously published work, providing additional evidence for the significance of genetic management units within oceanic populations of humpback whales.

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

DNA fingerprinting evidence of nonfilial nursing in grey seals - ELIZABETH A. PERRY; DARYL J. BONESS; ROBERT C. FLEISCHER (Molecular Ecology, 1998)
We tested the hypothesis that kin selection may play a role in fostering behaviour in grey seals. Fostering frequency varied among three colonies, ranging from 3% to 28%. Band‐sharing coefficients (S) of DNA fingerprints, from two multilocus probes, were used to predict relatedness ( r ). Mean r did not differ between foster mother‐pup pairs and the expected r = 0 for presumed unrelated female‐pup pairs. Likewise, mean r between fostered and filial pups compared to r between presumed unrelated pups within the same beaches did not differ. Mean S values of presumed unrelated pups on different beaches within the two smallest colonies were indistinguishable, indicating that there is not increased variation in relatedness in small colonies. These results suggest that kin selection does not play a significant role in the maintenance of grey seal fostering behaviour.

Increased metabolic cost of maintenance in hybrids of the stone crabs Menippe mercenaria and M. adina - C. A. Combs; R. P. Henry; T. M. Bert; H. M. Perry; M. West (Marine Biology, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Lead and PCB's in canvasback ducks: Relationship between enzyme levels and residues in blood - Michael P. Dieter; Matthew C. Perry; Bernard M. Mulhern (Archives of Environmental Contamination and Toxicology, 1977)

A plaque assay system for rinderpest virus and its use in characterising virus adsorption - W. P. Taylor; C. T. Perry (Archives of Virology, 1970)

Experimental infection of the argasid tick, ornithodoros moubata porcinus, with African swine fever virus - W. Plowright; C. T. Perry; M. A. Peirce; J. Parker (Archives of Virology, 1970)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)